The economic burden of meningitis to households in Kassena-Nankana district of Northern Ghana. - Patricia Akweongo (Public Library of Science (PLoS), 2013)
Objective To estimate the direct and indirect costs of meningitis to households in the Kassena-Nankana District of Ghana. Methods A Cost of illness (COI) survey was conducted between 2010 and 2011. The COI was computed from a retrospective review of 80 meningitis cases answers to questions about direct medical costs, direct non-medical costs incurred and productivity losses due to recent meningitis incident. Results The average direct and indirect costs of treating meningitis in the district was GH¢152.55 (US$101.7) per household. This is equivalent to about two months minimum wage earned by Ghanaians in unskilled paid jobs in 2009. Households lost 29 days of work per meningitis case and thus those in minimum wage paid jobs lost a monthly minimum wage of GH¢76.85 (US$51.23) due to the illness. Patients who were insured spent an average of GH¢38.5 (US$25.67) in direct medical costs whiles the uninsured patients spent as much as GH¢177.9 (US$118.6) per case. Patients with sequelae incurred additional costs of GH¢22.63 (US$15.08) per case. The least poor were more exposed to meningitis than the poorest. Conclusion Meningitis is a debilitating but preventable disease that affects people living in the Sahel and in poorer conditions. The cost of meningitis treatment may further lead to impoverishment for these households. Widespread mass vaccination will save households' an equivalent of GH¢175.18 (US$117) and impairment due to meningitis.